Os jogos sociomotrizes de cooperação e a construção de valores acerca da indisciplina discente - Pereira, Luiz Antonio (2020)
Indiscipline has emerged as a major educational problem and much has been discussed on this topic. Physical Education at school does not come out unscathed from this problem, facing everyday situations that are an obstacle to the smooth running of classes, impairing the learning of content and making it difficult to deepen the themes proposed by the teacher. We see in cooperative socio-motor activities - which offer experiences of participation in which the student has to seek, together with the others and solve situations in a collaborative way - the possibility that aspects related to solidarity, respect and empathy are present in the tasks development. Thus, the objectives of this research were to identify situations of indiscipline in an elementary school class and to analyze whether the experience and learning with cooperative socio-motor activities and activities aimed at building values could help students' perception and reflection about school indiscipline in Physical Education classes. The research was characterized by action research process and the instruments of data collection were: a) Class record books for the observation of situations of indiscipline during Physical Education classes and, b) Conversation circles, performed during in the beginning and in the end of classes. The teacher-researcher oversaw the students' experiences provided by didactic unit in order to understand whether they could link the proposed activities with the context of indiscipline in Physical Education classes. The work was carried out in a public school in the municipal teaching network of Matão / SP, with a class of 25 students from the 5th grade of elementary school. At the end of the research development, we reached the following analysis categories: 1) The indiscipline in Physical Education classes, which allowed us to identify the main problems of class indiscipline; 2) Construction of rules and attitudinal values: the pedagogical pact construction assemblies, during the intervention of the teacher-researcher; a proposal was made to confront indiscipline during the classes, promoting reflections and actions that were important in raising awareness of this issue; 3) Socio-motor cooperation activities displayed the importance of developing these games in Physical Education classes, as they have collaborative participation in their internal logic, which made it possible for the students to recognize the cooperative socio-motor activities and to identify their perceptions when performing them. We conclude that the cooperative socio-motor activities are important to confront indiscipline and - when accompanied by reflections on this problem - they can contribute to resolve / mitigate situations of this nature in Physical Education classes.